Stabilized polynuclear iron hydroxide is an efficient oral phosphate binder in uraemic patients - Hergesell, Olaf; Ritz, Eberhard (Nephrology, dialysis, transplantation, 1999)
There is a continuing need for non-aluminium and non-calcium-containing oral phosphate binders. A novel product, i.e. stabilized polynuclear iron hydroxide, has experimentally been shown to be an effective phosphate binder. The purpose of the study was to test the efficacy and tolerability of the compound in hyperphosphataemic patients with stable preterminal renal failure. er.
Gesehen am 05.11.2021